2011
DOI: 10.1007/s00018-011-0764-9
|View full text |Cite
|
Sign up to set email alerts
|

Cytoglobin: biochemical, functional and clinical perspective of the newest member of the globin family

Abstract: Since the discovery of cytoglobin (Cygb) a decade ago, growing amounts of data have been gathered to characterise Cygb biochemistry, functioning and implication in human pathologies. Its molecular roles remain under investigation, but nitric oxide dioxygenase and lipid peroxidase activities have been demonstrated. Cygb expression increases in response to various stress conditions including hypoxia, oxidative stress and fibrotic stimulation. When exogenously overexpressed, Cygb revealed cytoprotection against t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(72 citation statements)
references
References 130 publications
(291 reference statements)
1
70
0
1
Order By: Relevance
“…It was previously reported that Cygb associates with sodium oleate in a 1:1 ratio with a dissociation constant that ranges from 0.7 to 110 μM (Reeder et al, 2011). Fatty acids interactions with Cygb may be relevant for its physiological function since Cygb may have a role in fatty acid transport which could be related to its involvement in cancer (Oleksiewicz et al, 2011). In addition, the interaction of Cygb with fatty acids may be …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It was previously reported that Cygb associates with sodium oleate in a 1:1 ratio with a dissociation constant that ranges from 0.7 to 110 μM (Reeder et al, 2011). Fatty acids interactions with Cygb may be relevant for its physiological function since Cygb may have a role in fatty acid transport which could be related to its involvement in cancer (Oleksiewicz et al, 2011). In addition, the interaction of Cygb with fatty acids may be …”
Section: Discussionmentioning
confidence: 99%
“…Consequently, Cygb exhibits extended Nand C-termini, whereas Adgb only displays an extended N-terminus. The role of these extended termini in Cygb is not clear, but it has been proposed that they may be involved in association with lipids and/or protein-protein interactions (Oleksiewicz et al, 2011;Reeder et al, 2011). Conserved residues are represented by a star below the sequence, whereas residues that strongly share similar properties are represented by two dots and those exhibiting weak similarity are represented by one dot below the sequence.…”
Section: Heme Proteinsmentioning
confidence: 99%
See 3 more Smart Citations